CHALLENGES AND TASKS FOR THE MODERN MANAGER - RUDYKA, VIKTOR (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article presents the new challenges facing managers and the threats posed by modern areas of management. Given the global trends, new management technologies, other approaches to management decisions, domestic managers must implement in real life today. This is due to numerous internal and external factors that affect it. Senior managers take into account external factors that affect the organization, as it operates in conditions of instability. The main content of the work of managers is increasingly the transformation of existing knowledge into new ones and the rationalization of internal processes of creation, processing and transmission of information. For successful survival in the market and implementation of the development strategy, management must be flexible and dynamically developed. Continuous development, not only technological but also social, dynamic changes in economic conditions and increasing globalization, pose new challenges for managers, both in terms of functionality and personality. The survival of society depends on the quality of management, honesty, professionalism and values of managers and leaders. There are new requirements for modern management, new features of the manager who can effectively combine the role of a demanding boss with the participation of an inspirer, a far-sighted leader. Given the challenges of today, there is a need to outline new challenges for modern management and highlight its characteristics that have resulted from transformational processes, intellectualization of society, the growth of dynamic and unstable trends. The effectiveness of the formation and implementation of new management tasks can be ensured under at least two main conditions: it is necessary to take into account the peculiarities of previous development and the current state of the economy, mentality and characteristics of the country; it should be based on the principles and mechanism of management of countries with developed market economies. This will allow in the future to integrate the domestic economy into the world economic system, to take a worthy place in it.
Keywords: management; managers; organization; challenges; markets